Low-Temperature Processing of Titanium Oxide Nanoparticles Photoanodes for Dye-Sensitized Solar Cells - Al Dahoudi, Naji; Zhang, Qifeng; Cao, Guozhong (Journal of Renewable Energy, 2013)
Using the low-temperature processing of different organofunctional silanes like TEOS, GPTS, and MPTS to incorporate within TiO2 network, dye-sensitized solar cells (DSCs) processed at low temperatures were obtained. The UV-cured MPTS-modified layer exhibited better performance over the TEOS and GPTS, where better mechanical stable layer is achieved in addition to better interconnection between the TiO2 nanoparticles. The J-V characteristics of the DSC composed of silane-based layer showed that the improved cell performance was due to the high photocurrent density accompanied with more dye adsorption and higher charge injection from TiO2 to FTO substrate resulting from the formation of an ohmic contact with the substrate. The highest conversion efficiency attained for MPTS-TiO2 layer cured with UV and followed by heating at 300∘C was 3.75±0.07%, which is 2.8 times better than the GPTS-based layer.